Pelatihan LaTeX dan Kahoot untuk Meningkatkan Kemampuan Menulis Dokumen dan Pembuatan Soal Matematika yang Menarik bagi Guru-Guru Tingkat SMA di Kabupaten Bogor - Safniyeti Safniyeti (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The teacher is a science teacher with the main task of educating, teaching, guilding, directing, training, assessing, and evaluating students. One of the subjects that is considered complicated and difficult to convey to students is Mathematics. Mathematics is considered complicated both during the implementation of teaching and learning activities and when making documents because many formulas will be input and delivered to students. Mathematics is also considered as one of the boring subjects. This causes the teacher difficulties when delivering material to students. The LaTeX and Kahoot training activities are aimed at providing knowledge to high school Mathematics teachers about making interesting documents and Mathematics questions. The implementation of this training is the delivery of material and practice of making documents and Mathematics questions. Through this training it is expected to develop teacher is knowledge and skills on LaTeX and Kahoot applications and be able to apply in teaching and learning activities so as to improve teacher competency.